All types are called, but some are more likely to respond: the psychological profile of rural Anglican churchgoers in Wales. (3rd July 2014) - Francis, Leslie; Robbins, Mandy; Williams, Angela; Williams, Rhys
Abstract : In principle churches proclaim their invitation to worship to all sectors of the population. In practice some sectors appear more willing to respond. Alongside the more visible demographic bias in terms of sex and age, this study draws attention to the less visible bias in terms of psychological type. New data provided by 185 rural Anglican churchgoers who completed the Francis Psychological Type Scales demonstrated that there were significantly higher proportions of individuals reporting ISFJ and ESFJ preferences in church congregations than in the population of men and women at large.